2021
DOI: 10.1016/j.esmoop.2021.100104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on social media as perceived by the oncology community: results from a survey in collaboration with the European Society for Medical Oncology (ESMO) and the OncoAlert Network

Abstract: Background The COVID-19 pandemic has impacted all aspects of modern-day oncology, including how stakeholders communicate through social media. We surveyed oncology stakeholders in order to assess their attitudes pertaining to social media and how it has been affected during the pandemic. Materials and methods A 40-item survey was distributed to stakeholders from 8 July to 22 July 2020 and was promoted through the European Society for Medical Oncology (ESMO) and the Onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…21 The increased access to virtual oncology conferences and virtual mentorship programmes have also proven popular. 22 In the long-term, these initiatives may increase the ability of more staff to participate in professional development activities while balancing other commitments and mitigating financial cost.…”
Section: Discussionmentioning
confidence: 99%
“…21 The increased access to virtual oncology conferences and virtual mentorship programmes have also proven popular. 22 In the long-term, these initiatives may increase the ability of more staff to participate in professional development activities while balancing other commitments and mitigating financial cost.…”
Section: Discussionmentioning
confidence: 99%
“…The Meta study Page also connects survivors and family/friends of survivors with information to learn more about the study, breast cancer disparities, and the study investigators/team. Recent research has shown that cancer patients are now utilizing social media more during COVID-19 as a resource to answer questions related to their cancer experience ( 25 , 26 ). We have found that breast cancer survivors recruited through Meta share the study information and questionnaire directly with their social networks on social media and with individuals who might not have Meta accounts.…”
Section: Discussionmentioning
confidence: 99%
“…However, these platforms may help professionals collaborate with each other, participate in journal clubs and join online discussions. A recent study that included oncologists revealed that social media was especially preferred for networking, research sharing, and leadership development ( 16 ). On the other hand, YouTube was frequently used by the surgeons participating in our study.…”
Section: Discussionmentioning
confidence: 99%